2008
DOI: 10.1111/j.1939-1676.2008.0094.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe Thiamine Deficiency in Sheep with Acute Ruminal Lactic Acidosis

Abstract: Background: Thiamine status of ruminants is adversely affected in acidic rumen conditions. However, there have been limited published case study data related to thiamine deficiency of ruminants with acute ruminal lactic acidosis (ARLA).Hypothesis: Thiamine deficiency would occur in sheep with ARLA. Animals: Thirteen Ak-Karaman (white Karaman) sheep with ARLA, aged 1 year (ARLA group) and 10 healthy Ak-Karaman sheep, aged 1 year (control group) were used.Methods: After clinical examination, rumen fluid samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 11 publications
6
13
0
1
Order By: Relevance
“…The reported clinical signs of animals suffering from ruminal alkalosis were in accordance with Radostits et al, (2007), Karapinar et al (2008), Mohamed (2014) and Shah and Hussain (2017). Respiration rate were found to be significantly (p<0.001) increased whereas ruminal motility (p<0.001) decreased in animals with ruminal alkalosis.…”
Section: Clinical Findings Recorded In Sheep With Ruminal Disorderssupporting
confidence: 86%
See 1 more Smart Citation
“…The reported clinical signs of animals suffering from ruminal alkalosis were in accordance with Radostits et al, (2007), Karapinar et al (2008), Mohamed (2014) and Shah and Hussain (2017). Respiration rate were found to be significantly (p<0.001) increased whereas ruminal motility (p<0.001) decreased in animals with ruminal alkalosis.…”
Section: Clinical Findings Recorded In Sheep With Ruminal Disorderssupporting
confidence: 86%
“…In the present study, the protozoal motility of animals suffering from alkaline indigestion was analyzed and graded. Karapinar et al (2008) recorded similar findings in sheep with alkalosis. The reason for the development altered protozoal motility might be due to improper utilization and storage of glycogen by rumen protozoa affected by toxic levels of ammonia.…”
Section: Physical and Other Characteristics Of Ruminal Fluid Among Rusupporting
confidence: 60%
“…Thiamine pyrophosphate participates in the decarboxylation of keto acids and is also a coenzyme of transketolase. These enzymes play significant roles, especially in the metabolism of carbohydrates and independent specific roles in neurophysiology [4,19,20]. Therefore, thiamine deficiency causes a wide range of clinical appearances from anorexia to polioencephalomalacia because of the numerous functions of thiamine, which has been observed in the current study.…”
Section: Discussionsupporting
confidence: 62%
“…Under anaerobic condition, PFL is a central enzyme to degrade pyruvate to acetyl-CoA and the enzyme comprises the cofactors S-adenosylmethionine and thiamine diphosphate (TPP) (Knappe et al 1969 ). As the cofactor of PFL, thiamine content was detected significantly decreased when feeding SAID diet (Karapinar et al 2008 ; Pan et al 2016 ). As a result, the conversion of pyruvate to acetyl-CoA was restrained, and the superfluous pyruvate were then converted to lactate by lactate-producing bacteria such as S. bovis (Asanuma and Hino 2000 ) through LDH, which led to accumulation of lactate and SARA aggravation in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our previous study revealed that thiamine supplementation could attenuate high-concentrate diet induced SARA by decreasing ruminal lactate production and increasing ruminal pH value in rumen fluid (Pan et al 2016 ). The possible reason was that thiamine supplementation promoted carbohydrate metabolism, since thiamine is the coenzyme of pyruvate dehydrogenase (PDH) and α-ketoneglutaric acid dehydrogenase (α-KGDHC) in carbohydrate metabolism (Miller et al 1986 ; Karapinar et al 2008 ). However, it was not clear how thiamine supplementation affected the ruminal nutrient metabolism systematically in dairy cows.…”
Section: Introductionmentioning
confidence: 99%